Effects of tuberization conditions on the microtuber yield and on the proportion of microtuber tissues - J. Dobránszky; K. Magyar-Tábori (International Journal of Horticultural Science, 2004)
The production facilities of large-sized microtubers in three potato varieties (cv. Desiree, BorO, Gfilbaba) and the effects of the applied tuberization conditions on the proportion of microtuber tissues, especially on the perimedullary region were investigated in present work. In vitro tuberization was induced on explants with 2 or 5 nodes layered on MS medium supplemented with 8% sucrose. Induced cultures were exposed to short days (8 h) for 2 weeks, then to total darkness for further 11 weeks. For volume calculations of different tissue regions, the formula for ellipsoids (V=4/37c1/8/w2) was used. The number of large-size tubers (> 8 mm, up to 16 mm) reached 53%, 59% and 44% in cvs. Desiree, Giilbaba and Bore, respectively, which indicate that the size of microtubers could be increased by appropriate sucrose support and explant type. Microtubers produced on hormone-free medium have well-developed perimedullary region, and its volume rate seemed to be important in the final size of tubers. The increase in the rate of volume of the perimedulla was connected to the increase of tuber size until tubers reached 12 mm diameter. In microtubers larger than 12 mm in diameter, the volume rate of the pith was increased.